PHAGOCYTIC ACTIVITY OF PERIPHERAL BLOOD NEUTROPHILS IN MECHANISMS OF EXPERIMENTAL BACTERIAL-IMMUNE PERIODONTITIS DEVELOPMENT - Demkovych, A.Ye.; Bondarenko, Yu.I.; Hasiuk, P.A.; Sukhovolets, I.O. (World of Medicine and Biology, 2020)
One of the important links that leads to injure in all structures of the periodontium and formation of inflammation of varies severity is phagocytic activity of polymorphonuclear leukocytes. The purpose of the study was to evaluate pathogenic role of neutrophils activity in the experimental bacterial-immune inflammation in periodontium. The article shows the results of studies on the spontaneous and activated test with nitroblue tetrazolium on the 7th, 14th and 30th days of the bacterial-immune inflammation in periodontal tissues. In this paper, the results of neutrophils activity changes in the process of formation and chronification of the inflammation in the tissues of periodontal complex are presented. It was established that the nature of the experimental inflammation course in periodontal tissues depending on the peculiarities of phagocytic activity changes in blood neutrophils. In this condition the spontaneous test with nitro blue tetrazolium of blood neutrophils accompanied the growth and indices of the oxygen-dependent metabolism reserve decreased in the induced nitro blue tetrazolium test, the coefficient of blood neutrophils metabolic activation in the rats with inflammatory process in periodontium and testified about metabolic reserves depletion of these cells and disorder of phagocytic activity.
Keywords: phagocytosis; bacterial-immune periodontitis; neutrophils; immune system